Penerapan Metode Profile Matching Pada Perekrutan Karyawan untuk PT. Dinasti Motekar Group - Dedi Liyus Mardi (Universitas Multimedia Nusantara, 2021)
Human resources are particularly important factor in any corporation to support the successful corporation. Employee recruitment is a thing that is not separated from a human resources management activity. To have employee fit expectation of corporation, the right employee recruitment system is necessary to have employee in accordance with his or her expertise. In the process of employee recruitment, a supporting decision system is required. Method used to make the employee recruitment system is using Profile Matching. In this study is raised a cases; i.e. seeking for the best alternative for the recruitment of employee in PT. Dinasti Motekar Group. The Profile Matching was chosen as it can establish weight grade for each attribute, then it is continued by the ranking process to be able to select the best alternative from other alternatives. The best alternative, therefore, might be acquired based on specific criteria as they were established by the corporation. Index Terms—Employee Recruitment; Decision Support System; Profile Matching.